ISOLATED MACULOPATHY AND MODERATE ROD–CONE DYSTROPHY REPRESENT THE MILDER END OF THE RDH12-RELATED RETINAL DYSTROPHY SPECTRUM. Issue 6 (June 2021) - De Zaeytijd, Julie; Van Cauwenbergh, Caroline; De Bruyne, Marieke; Van Heetvelde, Mattias; De Baere, Elfride; Coppieters, Frauke; Leroy, Bart P.
Abstract : Purpose: To describe an isolated maculopathy and an intermediate rod–cone dystrophy phenotype as the milder end of the RDH12 -related retinal dystrophy spectrum. Methods: Seven patients (17–34 years of age) underwent an extensive ophthalmic workup including psychophysical and electrophysiological testing and multimodal imaging. Results: Three patients have isolated macular disease. Best-corrected visual acuity (BCVA) ranges from 20/125 to 20/40 with normal visual fields or only limited central, relative scotomata, and normal full-field ERGs. Both optical coherence tomography scans and autofluorescent imaging hint at relatively better-preserved foveal quality initially. An intermediate rod–cone phenotype in four patients is characterized by a central retinal dystrophy extending just beyond the vascular arcades, characteristic peripapillary sparing, and additional scattered atrophic patches. Again, foveal quality is initially better on optical coherence tomography scans. Best-corrected visual acuity ranges from counting fingers to 20/32. Goldmann visual fields vary from central scotomata to severe generalized abnormalities. ERGs range between mild and severe rod–cone dysfunction. Nine distinct RDH12 pathogenic variants, two of which are novel, are identified. Conclusion: The classic phenotype of RDH12 -related early-onset retinal dystrophy is expanded to include an isolated maculopathy and intermediate dystrophy phenotype, characterized by its later onset and milder course with a fair visual potential until much later in life, emphasizing the phenotypic heterogeneity of RDH12 -related retinopathy. Abstract : Supplemental Digital Content is Available in the Text. RDH12 -related early-onset retinal dystrophy is a severe form of retinal dystrophy with major impact on visual function from the first years of life. We describe a maculopathy and an intermediate rod–cone dystrophy, representing the milder end of the RDH12 -related disease spectrum. Patients with these phenotypes have a better clinical prognosis.